The role of tourism media in activating Electronictourism - Dr. Mohan Shaalan Abbas (Peerian Journals Publishing, 2023)
This research aims to reveal the role of tourism media in activating the electronic tourism movement in Iraq and the extent of media interest in local tourism through the use of electronic media. Several axes and investigations, and the first topic dealt with the introduction and methodology of the study. The methodology included the research problem, importance, objectives, hypothesis, study, and study determinants. Then came the field work and contained the analytical descriptive approach and the field approach, As for the second topic, it included the independent variable (tourist media) in terms of importance, goals, elements of tourism media, the media message and its importance, as well as the media used in tourism media work , As for the third topic, it dealt with the dependent variable (e-tourism) in terms of the concept, importance, ingredients, and ways of success of electronic-tourism, as well as the obstacles that stand in the way of achieving the success of e-tourism. The last thing that came in this topic are the benefits of e-tourism , As for the fourth topic, which is the last topic, it included the applied and analytical descriptive side of the questionnaire data, extracting the arithmetic mean, standard deviation, and relative importance, as well as conclusions, recommendations, and appendices
Keywords: Electronic-tourism; media; tourism media